A negative electrode with controllable grain size and a preparation method thereof
Patent Information
- Application Number
- CN202511722098.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-11-21
AI Technical Summary
[0009]本发明的目的在于克服现有技术中高温预锂化过程中硅氧材料(SiOx)与锂源反应导致硅晶粒尺寸增大、电池综合性能下降的缺陷,提供一种晶粒尺寸可控负极及其制备方法
1.有效控制晶粒尺寸:采用原位碳包覆工艺,碳源(萘)在高温下熔化吸热,可显著降低锂源与SiOx反应释放的热量,避免局部过热导致硅和偏硅酸锂晶粒过度生长;实验数据表明,与未添加碳源的对比例相比,本发明制备的负极材料中硅晶粒尺寸减小20-30%,偏硅酸锂晶粒尺寸减小5-10%,更小的晶粒尺寸可分散充放电过程中的应力,缓解体积膨胀,提升循环稳定性。
Smart Images

Figure CN121573681B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of secondary battery materials technology, specifically a negative electrode with controllable grain size and its preparation method. Background Technology
[0002] With the rapid development of science and technology, non-renewable resources such as oil and coal are becoming increasingly depleted, leading to more and more severe environmental pollution problems. Developing renewable clean energy and new energy storage systems has become an urgent priority. Lithium-ion batteries, with their significant advantages such as high energy density and long cycle life, are widely used in many areas of daily life.
[0003] Currently, traditional commercial lithium-ion batteries mainly consist of cathode materials such as ternary lithium (theoretical specific capacity 276 mAh / g) and lithium iron phosphate (theoretical specific capacity 170 mAh / g) and a graphite anode (theoretical specific capacity 372 mAh / g). However, the actual specific capacity of the graphite anode is approaching its theoretical limit, making it difficult to meet people's demand for high-energy-density lithium-ion batteries.
[0004] Silicon-oxygen compounds (SiOx) possess a high theoretical specific capacity of 2400 mAh / g, and their preparation process is simple and inexpensive. They are also less prone to lithium plating during charge and discharge. Compared to silicon (Si, with a theoretical specific capacity of 4200 mAh / g but a volume expansion rate as high as 300%), silicon-oxygen compounds exhibit a significantly lower volume expansion rate (approximately 200%), while also possessing superior cycle performance and rate capability. It is the first silicon-based anode material to achieve commercial application.
[0005] Despite the significant advantages and rapid development of silicon-oxygen materials, large-scale commercial applications still face numerous challenges, with low initial coulombic efficiency being one of the core issues. The main reason for the low initial coulombic efficiency of silicon-oxygen materials is that during the first charge and discharge process, lithium ions (… It will react with silicon-oxygen materials to generate various lithium silicates ( , , ) and lithium oxide ( This process consumes a large number of lithium ions; at the same time, the repeated formation of the solid electrolyte interphase (SEI) film during the initial charge and discharge process leads to huge irreversible capacity loss, which in turn significantly reduces the first coulombic efficiency (ICE) of silicon-oxygen materials.
[0006] To address the low initial coulombic efficiency of silicon-oxygen materials, early researchers employed various lithium sources through a solid-state pre-lithiation process to compensate for irreversible lithium loss during the first charge-discharge cycle. However, as the pre-lithiation temperature increases, the silicon grain size inevitably enlarges, leading to a significant decrease in the battery's overall performance (such as cycle stability and rate performance).
[0007] A current Chinese patent (application number: CN118598143B) discloses "A carbon-coated low-temperature molten salt technique for preparing pre-lithiated silicon suboxide and its application in energy storage batteries." This technique involves mixing silicon suboxide with lithium salt and then sintering the mixture in molten salt to obtain a pre-lithiated material. This pre-lithiated material is then mixed with a solid carbon source and calcined to finally obtain the pre-lithiated silicon suboxide material. While this technique can achieve materials with high initial coulombic efficiency, the "pre-lithiation followed by carbon coating" process inevitably leads to coarsening of silicon grains during the secondary carbon coating process, thus affecting the overall performance of the battery.
[0008] Therefore, there is an urgent need to develop a new technical solution that can effectively suppress the growth of silicon and lithium silicate grains while achieving pre-lithiation of silicon-oxygen materials to improve the first coulombic efficiency, thereby ensuring the overall performance of the battery. Summary of the Invention
[0009] The purpose of this invention is to overcome the shortcomings of existing technologies where the reaction between silicon-oxygen materials (SiOx) and the lithium source during high-temperature pre-lithiation leads to increased silicon grain size and decreased overall battery performance. This invention provides a negative electrode with controllable grain size and its preparation method. Through an in-situ carbon coating process, carbon coating is simultaneously achieved during pre-lithiation, effectively reducing the grain size of silicon and lithium metasilicate, adjusting the content of silicon and lithium metasilicate phases, and simultaneously forming an amorphous carbon layer that improves material conductivity, suppresses volume expansion, and ultimately improves battery cycle stability and initial coulombic efficiency.
[0010] This invention is achieved through the following technical solution: A method for preparing a negative electrode with controllable grain size includes the following steps: S1 Raw Material Mixing: The ratio of lithium source to SiOx is determined according to a molar ratio of 0.1-0.7. x To obtain a mixture, a carbon source is added to the mixture of lithium source and SiOx, wherein the mass of the carbon source is 5-10 wt% of the total mass of lithium source and SiOx. The mixture is then thoroughly mixed to obtain a mixture.
[0011] S2 In-situ pre-lithiation and carbon coating: The mixture obtained in step S1 is loaded into a sintering boat, and the sintering boat is moved into a tube furnace; inert gas is introduced into the tube furnace, and the temperature is raised to 600-800℃ at a heating rate of 1-10℃ / min, held for 2-10h, and then naturally cooled to obtain a negative electrode material with controllable grain size.
[0012] Furthermore, the lithium source is one or more of lithium hydride, lithium hydroxide, and lithium carbonate.
[0013] Furthermore, the carbon source is naphthalene. Naphthalene can melt and absorb heat at high temperatures, suppressing local overheating during the reaction between the lithium source and SiOx. At the same time, naphthalene can carbonize in an inert gas atmosphere to form an amorphous carbon layer that coats the surface of the negative electrode material.
[0014] Furthermore, the inert gas is one or more of helium and argon. The inert gas prevents the raw materials and products from being oxidized at high temperatures, ensuring the stability of the reaction.
[0015] This invention also protects a negative electrode material with controllable grain size obtained by the above preparation method. The negative electrode material includes silicon, lithium metasilicate, lithium disilicate, lithium orthosilicate, and an amorphous carbon layer. The relative content of silicon is 28-32%, the lattice spacing of silicon is mainly 0.31 nm, and the silicon grain size is 8-13 nm. The relative content of lithium metasilicate is 58-64%, the lattice spacing of lithium metasilicate is mainly 0.33 nm, and the lithium metasilicate grain size is 9-20 nm.
[0016] Furthermore, the lithium metasilicate accounts for ≥94% of the total amount of lithium silicate.
[0017] Furthermore, the thickness of the amorphous carbon layer is 10-14 nm.
[0018] In this invention, lithium metasilicate (Li2SiO3) has the best mechanical buffering capacity among various lithium silicates, and the formation of more Li2SiO3 can effectively improve the stability of the material; lithium disilicate (Li2Si2O5) is the only reversible lithium silicate phase, which can improve the first coulombic efficiency of the material; lithium orthosilicate (Li4SiO4) is unstable in air and humid environments and easily reacts to form lithium carbonate (Li2CO3) and lithium hydroxide (LiOH).
[0019] In this invention, the grain size of Si and Li2SiO3 is calculated by taking the average value of the peak areas of each crystal plane from the XRD diffraction pattern. Smaller grain sizes result in more dispersed stress, significantly mitigating the volume expansion effect and improving cycle stability.
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. Effective control of grain size: The in-situ carbon coating process is adopted, and the carbon source (naphthalene) melts and absorbs heat at high temperature, which can significantly reduce the heat released by the reaction between the lithium source and SiOx, and avoid excessive growth of silicon and lithium metasilicate grains due to local overheating. Experimental data show that compared with the control group without carbon source, the silicon grain size in the negative electrode material prepared by this invention is reduced by 20-30%, and the lithium metasilicate grain size is reduced by 5-10%. The smaller grain size can disperse the stress during the charge and discharge process, alleviate volume expansion, and improve cycle stability.
[0021] 2. Improved conductivity and cycle performance: The amorphous carbon layer (10-14 nm thick) formed by carbonization of naphthalene in an inert gas atmosphere tightly coats the surface of the negative electrode material. On the one hand, it can significantly reduce the charge transfer impedance of the material (impedance testing shows that the semi-circular impedance in the high-frequency region of the material of this invention is 30-40% lower than that of the comparative example), thus improving conductivity. On the other hand, it can suppress the side reactions between the active material and the electrolyte, reduce the repeated formation of the SEI film, and reduce irreversible capacity loss.
[0022] 3. Optimization of lithium silicate phase composition: This invention achieves a lithium metasilicate ratio of ≥94% in total lithium silicate through process parameter control, fully leveraging its excellent mechanical buffering effect; at the same time, an appropriate amount of lithium disilicate is retained to ensure the initial coulombic efficiency of the material; experiments show that the anode material prepared by this invention can maintain a capacity retention of 77.1-90.4% after 100 cycles at 0.5C rate, which is much higher than the comparative ratio without added carbon source (51.8-51.9%).
[0023] 4. Simple process and easy to industrialize: The preparation process of this invention only involves two core steps: raw material mixing and high temperature insulation. It does not require complicated equipment, is easy to operate, and the reaction conditions are easy to control, making it suitable for commercial mass production. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of the present invention and should not be considered as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort. In the drawings: Figure 1 The graphs show the cycling performance of Examples 2-3 and Comparative Examples 2-3 at 0.5C.
[0025] Figure 2 This is the X-ray diffraction pattern of Example 1.
[0026] Figure 3 This is the X-ray diffraction pattern of Example 3.
[0027] Figure 4 This is the X-ray diffraction pattern of Comparative Example 1.
[0028] Figure 5 This is the X-ray diffraction pattern of Comparative Example 3.
[0029] Figure 6 This is the X-ray diffraction pattern for Comparative Example 4.
[0030] Figure 7 The heat flow curves are for Example 3 and Comparative Example 3.
[0031] Figure 8 Impedance diagrams for Example 3 and Comparative Example 3. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the embodiments and accompanying drawings. The illustrative embodiments and descriptions of the present invention are only used to explain the present invention and are not intended to limit the present invention.
[0033] A method for preparing a negative electrode with controllable grain size includes the following steps: S1 Raw Material Mixing: The ratio of lithium source to SiOx is determined according to a molar ratio of 0.1-0.7. x To obtain a mixture, a carbon source is added to the mixture of lithium source and SiOx, wherein the mass of the carbon source is 5-10 wt% of the total mass of lithium source and SiOx. The mixture is then thoroughly mixed to obtain a mixture.
[0034] S2 In-situ pre-lithiation and carbon coating: The mixture obtained in step S1 is loaded into a sintering boat, and the sintering boat is moved into a tube furnace; inert gas is introduced into the tube furnace, and the temperature is raised to 600-800℃ at a heating rate of 1-10℃ / min, held for 2-10h, and then naturally cooled to obtain a negative electrode material with controllable grain size.
[0035] Furthermore, the lithium source is one or more of lithium hydride, lithium hydroxide, and lithium carbonate.
[0036] Furthermore, the carbon source is naphthalene. Naphthalene can melt and absorb heat at high temperatures, suppressing local overheating during the reaction between the lithium source and SiOx. At the same time, naphthalene can carbonize in an inert gas atmosphere to form an amorphous carbon layer that coats the surface of the negative electrode material.
[0037] Furthermore, the inert gas is one or more of helium and argon. The inert gas prevents the raw materials and products from being oxidized at high temperatures, ensuring the stability of the reaction.
[0038] This invention also protects a negative electrode material with controllable grain size obtained by the above preparation method. The negative electrode material includes silicon, lithium metasilicate, lithium disilicate, lithium orthosilicate, and an amorphous carbon layer. The relative content of silicon is 28-32%, the lattice spacing of silicon is mainly 0.31 nm, and the silicon grain size is 8-13 nm. The relative content of lithium metasilicate is 58-64%, the lattice spacing of lithium metasilicate is mainly 0.33 nm, and the lithium metasilicate grain size is 9-20 nm.
[0039] Furthermore, the lithium metasilicate accounts for ≥94% of the total amount of lithium silicate.
[0040] Furthermore, the thickness of the amorphous carbon layer is 10-14 nm.
[0041] Example 1 A method for preparing a silicon-oxygen anode with controllable grain size includes the following steps: Weigh a certain mass of SiO x And lithium hydride, then add lithium hydride and SiO x 8% of the total amount of naphthalene. After thorough mixing in a glove box, transfer to a covered flaking boat. Incubate under an argon atmosphere at 10... o Cmin -1 The temperature rose to 700 o C, and keep warm for 6 hours.
[0042] Example 2 A method for preparing a silicon-oxygen anode with controllable grain size includes the following steps: Weigh a certain mass of SiO x And lithium hydride, then add lithium hydride and SiO x 8% of the total amount of naphthalene. After thorough mixing in a glove box, transfer to a covered flaking boat. Incubate under an argon atmosphere at 10... o Cmin -1 The temperature rose to 750. o C, and keep warm for 6 hours.
[0043] Example 3 A method for preparing a silicon-oxygen anode with controllable grain size includes the following steps: Weigh a certain mass of SiO x And lithium hydride, then add lithium hydride and SiO x 8% of the total amount of naphthalene. After thorough mixing in a glove box, transfer to a covered flaking boat. Incubate under an argon atmosphere at 10... o Cmin -1 The temperature rose to 800 o C, and keep warm for 6 hours.
[0044] Comparative Example 1 This comparative example is basically the same as Experimental Example 1, except that naphthalene is not added.
[0045] Weigh a certain mass of SiO x And lithium hydride. After mixing thoroughly in a glove box, transfer to a covered sintering boat. Incubate at 10°C under an argon atmosphere. o Cmin -1 The temperature rose to 700 o C, and keep warm for 6 hours.
[0046] Comparative Example 2 This comparative example is basically the same as Experimental Example 2, except that naphthalene is not added.
[0047] Weigh a certain mass of SiO x And lithium hydride. After mixing thoroughly in a glove box, transfer to a covered sintering boat. Incubate at 10°C under an argon atmosphere. o Cmin -1 The temperature rose to 750. o C, and keep warm for 6 hours.
[0048] Comparative Example 3 This comparative example is basically the same as Experimental Example 3, except that naphthalene is not added.
[0049] Weigh a certain mass of SiO x And lithium hydride. After mixing thoroughly in a glove box, transfer to a covered sintering boat. Incubate at 10°C under an argon atmosphere. o Cmin -1 The temperature rose to 800 o C, and keep warm for 6 hours.
[0050] Comparative Example 4 This comparative example is basically the same as Experimental Example 3, except that lithium is added first and then naphthalene is added. Weigh a certain mass of SiO x And lithium hydride. After mixing thoroughly in a glove box, transfer to a covered sintering boat. Incubate at 10°C under an argon atmosphere. o Cmin -1 The temperature rose to 800 o C, and keep at that temperature for 6 hours. Then, add lithium hydride and SiO2 to the obtained pre-lithiated material. x 8% of the total naphthalene was mixed evenly and then heated under an argon atmosphere at 5°C. o Cmin -1 The temperature rose to 800 o C, and keep warm for 2 hours. The negative electrode materials obtained in Examples 2-3 and Comparative Examples 2-3 were used as active materials, conductive carbon black (Sup-p) and carbon nanotubes (SWCNT) were used as conductive agents, and styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) were used as binders in a ratio of 91:2.4:0.1:5:1.5. The uniformly stirred slurry was coated onto copper foil and dried in a vacuum drying oven at 80°C. o Incubate at C for 12 hours. After slicing, assemble the CR-2032 button half-cell in a glove box under argon atmosphere, following the order of positive electrode material, electrolyte, separator, electrolyte, lithium sheet, gasket, and spring contact, with the lithium sheet serving as the counter electrode. The test voltage was 0.01V to 1.5V, and the current density was 0.5C.
[0051] Figure 1The graphs show the cycling performance of Examples 2-3 and Comparative Examples 2-4 at 0.5C. As shown in the graphs, after 100 cycles, Comparative Examples 2-4 retained 51.9%, 51.8%, and 70.0% capacity, respectively, while Examples 2-3 retained 77.1% and 90.4% capacity, respectively. This indicates that the cycling performance of materials coated with naphthalene in situ is significantly improved, and all are better than materials at the same temperature. Among them, Example 3 exhibits superior cycling performance compared to Comparative Example 4. This is because the effective endothermic reaction during naphthalene carbonization creates a milder environment for silicon grain growth, thereby inhibiting Si grain size growth and effectively improving the cycling stability of the silicon-oxygen battery.
[0052] Figure 2 The X-ray diffraction patterns are shown for Examples 1 and 3, and Comparative Examples 1, 3, and 4. The figures show that the peak intensities of various phases in Examples 1 and 3, and Comparative Examples 1, 3, and 4, changed after high-temperature solid-state sintering. The relative content of lithium metasilicate (Li₂SiO₃) in Examples 1 and 3 was higher than that in Comparative Examples 1 and 3, indicating that the addition of naphthalene can effectively form more Li₂SiO₃, thereby improving the stability of the material. Furthermore, a comparison of the XRD patterns of Examples 3 and Comparative Example 4 reveals that only in-situ carbon coating can change the XRD peak intensity. Based on the Scherrer formula, we obtained the average grain sizes of silicon and lithium metasilicate, as shown in Table 1. By comparison, we can see that the grain sizes of Si and Li₂SiO₃ gradually increase with increasing temperature. Specifically, the silicon grain size in Example 1 is 8.9 nm, and the lithium metasilicate grain size is 14.4 nm; the silicon grain size in Comparative Example 1 is 12.0 nm, and the lithium metasilicate grain size is 15.2 nm. In Example 3, the silicon grain size was 12.4 nm and the lithium metasilicate grain size was 19.2 nm; in Comparative Example 3, the silicon grain size was 15.2 nm and the lithium metasilicate grain size was 21.0 nm. In Comparative Example 4, the silicon grain size was 15.8 nm and the lithium metasilicate grain size was 20.6 nm. The comparison demonstrates that in-situ carbon coating can effectively reduce the grain size of silicon and lithium metasilicate, thereby increasing the cycling stability of the material. However, the method of pre-lithiation followed by carbon source coating cannot effectively inhibit the growth of silicon and lithium metasilicate grains, and may even promote Si grain growth.
[0053]
[0054] Figure 6 The figures show the heat flow curves for Example 3 and Comparative Example 3. The comparison shows that Example 3 has a smaller exothermic peak, indicating that the addition of naphthalene during the heating process effectively reduces the heat released by the reaction, thus making the growth of Si and Li2SiO3 grains more gradual and inhibiting the growth of Si and Li2SiO3 grain sizes.
[0055] Figure 7 The impedance diagrams for Example 3 and Comparative Example 3 are shown. A comparison of the diagrams reveals that Example 3 exhibits the lowest semicircular impedance in the high-frequency region, indicating that Example 3 possesses the lowest charge transfer impedance. This demonstrates that the in-situ carbon coating formed by naphthalene effectively increases the conductivity of the material.
[0056] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a negative electrode material with controllable grain size, characterized in that, Includes the following steps: S1 Raw material mixing: Determine the mass of lithium source and SiOx according to the molar ratio of lithium source to SiOx of 0.1-0.7, add carbon source to the mixture of lithium source and SiOx, the mass of carbon source is 5-10 wt% of the total mass of lithium source and SiOx, mix evenly to obtain a mixture. S2 In-situ pre-lithiation and carbon coating: The mixture obtained in step S1 is loaded into a sintering boat, and the sintering boat is transferred into a tube furnace; inert gas is introduced into the tube furnace, and the temperature is raised to 600-800℃ at a heating rate of 1-10℃ / min, held for 2-10h, and then naturally cooled to obtain a negative electrode material with controllable grain size. The lithium source is one or more of lithium hydride, lithium hydroxide, and lithium carbonate; The carbon source is naphthalene; The inert gas is one or more of helium and argon.
2. The anode material with controllable grain size obtained by the preparation method according to claim 1, characterized in that, The negative electrode material includes silicon, lithium metasilicate, lithium disilicate, lithium orthosilicate, and an amorphous carbon layer; the relative content of silicon is 28%-32%, the lattice spacing of silicon is mainly 0.31nm, and the silicon grain size is 8-13nm; the relative content of lithium metasilicate is 58%-64%, the lattice spacing of lithium metasilicate is mainly 0.33nm, and the lithium metasilicate grain size is 9-20nm.
3. The grain size controllable negative electrode material according to claim 2, characterized in that, The proportion of lithium metasilicate in the total amount of lithium silicate is ≥94%.
4. The grain size controllable negative electrode material according to claim 3, characterized in that, The thickness of the amorphous carbon layer is 10-14 nm.
Citation Information
Patent Citations
A carbon-coated low-temperature molten salt technology for preparing pre-lithiated silicon oxide and its application in energy storage batteries
CN118598143B
High temperature solid state preparation method of lithium ion battery cathode material lithium metasilicate
CN104022282A
Negative pole piece, electrochemical device comprising negative pole piece and electronic device
CN116806375A